2015
DOI: 10.1016/j.egypro.2015.07.534
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Single Effect Solar Absorption Cooling System (Libr-H2O)

Abstract: Fossil fuels are on the verge of depletion, and the world energy consumption is in constant progression, resulting in very serious concerns about environmental issues. Mechanical refrigeration based on vapor compression principle uses high grade electrical energy, and refrigerant fluid with a global worming and ozone depletion potentials.Absorption machines using solar thermal energy are excellent alternatives to mechanical refrigeration. Absorption cooling systems are mature technologies that proved their abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…The mathematical model represented in [11] for H 2 0/LiBr operation predicts COP th = 0.77 for T s = 90 ºC, T c = 40 ºC and T AC = 7 ºC, this set of conditions repeats the data of the experimental measurements in Finland [3] with very similar thermal COP considered above. However, this model does not cover electrical energy consumption expressed by ESF or EER.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…The mathematical model represented in [11] for H 2 0/LiBr operation predicts COP th = 0.77 for T s = 90 ºC, T c = 40 ºC and T AC = 7 ºC, this set of conditions repeats the data of the experimental measurements in Finland [3] with very similar thermal COP considered above. However, this model does not cover electrical energy consumption expressed by ESF or EER.…”
Section: Methodssupporting
confidence: 54%
“…Balancing the absorption chiller output and the cooling power consumption is possible by using the cold water storage 6 in Fig.2. The calculation results according to equations (10)(11)(12) and the experimental data [3] are presented in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] The efficiency of absorption cooling systems can further be improved by two to three times by adopting a solar steam regeneration method on absorbent solutions. 33 Ketfi et al 34 calculated that the COP of a 70 kW Yazaki absorption cooling machine working with water-lithium bromide mixture, has reached a maximum of 0.77 at a generator temperature of 92 C. Two generators coupled in series to increase the amount of refrigerant vapour for an equivalent amount of heat input in a series flow double effect LiBr-H 2 O absorption system. 35 It observed that double-effect systems have a higher COP value of 1-1.28 than the single effect absorption systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical methods were employed to calculate solar collector efficiency in order to be used as an input parameter in transient system software or analytical methods for solar cooling systems [5,18]. In most research, thermal efficiency was calculated without taking into account the flowrate of the solar collector, which affects the accuracy of the overall evaluation of the solar cooling system.…”
Section: Introductionmentioning
confidence: 99%